A Grey-based DEMATEL approach for analyzing the strategies of universities: A case of Turkey - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2015)
One of the most important points in strategic planning process is the selection of strategies. This due to the reason that strategies are usually related to each other which increases the complexity. In this study, we present an approach named as grey-based DEMATEL method for analyzing and evaluating the strategies for universities. The use of grey systems theory together with DEMATEL method is an effective and successfull approach since it can integrate uncertainty and ambiguity into the evaluation process based on subjective judgements. The aim of this method is analyzing and revealing the causal relationships among strategies, and also prioritizing these strategies according to their level of influence. © 2015 IEEE.
Keywords: DEMATEL; grey systems; university strategies